Memory window enhancement in n-type ferroelectric field-effect transistors by engineering ozone exposure in atomic layer deposition of HfZrOx films - 전지훈; Kuk, Song-Hyeon; 조아진; Baek, Seung-Hyub; Kim, Sang-Hyeon; Kim, Seong Keun (American Institute of Physics, 2023)
We demonstrate n-type ferroelectric field-effect transistors (FeFETs) employing atomic-layer-deposited HfZrOx (HZO) films with a large memory window (MW) immediately after the write operation. Charge trapping at the HZO/Si interface in FeFETs is the primary source of memory window reduction. To control the properties of the interfacial layer, we varied the O3 injection time during atomic layer deposition. The HZO (long O3 of 7？s)-based FeFET demonstrated a large MW (2.1？V) in the DC transfer curves compared with the HZO (short O3 of 0.3？s)-based FeFET (0.9？V), although the bulk properties of the HZO films barely changed with the O3 injection time. In pulsed I？V measurements with an extremely short delay time of 100？ns between pulses, the HZO (long O3 of 7？s)-based FeFET showed a large MW of 1.0？V. Such improvements in the performance of HZO-based FeFETs indicate that the trap density in the interfacial layer is reduced by the use of a long O3 injection time. This is supported by the variation in the silicate/SiO2 ratio within the interfacial layer of the HZO films deposited at various O3 injection times.